2022
DOI: 10.1088/1755-1315/1107/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Growth analysis of sweet corn plants treated with a soil amendment

Abstract: This study examined the effect of Zeolite soil amendment on performance (growth and yield) of sweet corn.The experiment was carried out in rice fields in KP. Mojosari, Mojosari District, Mojokerto Regency in MK II 2021 (April to September 2021), with 10 fertilization treatments which are the combination of the best Zeolite soil improver fertilization dose on sweet corn plants, including treatment A (control), B (Urea 200 kg/ha, ZA 100 kg/ha, NPK 275 kg/ha, without Zeolite), C (Urea 200 kg/ha, ZA 100 kg/ha, NPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…At the beginning of growth, namely the observation at 14 DAP did not show a significant increase in leaf area and was strongly influenced by the development of the number of leaves per plant (Table 5). According to the results research by Aisyawati et al (2022) that, the lowest leaf area per plant was found in the treatment without fertilization (treatment A), while between other fertilization treatments there was no significant difference [22]. This shows that the land used is less fertile so it is very IOP Publishing doi:10.1088/1755-1315/1253/1/012023 6 responsive to the application of fertilizer, although the variation in the increase in leaf area per plant is not significantly different between the doses of fertilization given to sweet corn plants.…”
Section: Plant Growth and Yieldmentioning
confidence: 88%
“…At the beginning of growth, namely the observation at 14 DAP did not show a significant increase in leaf area and was strongly influenced by the development of the number of leaves per plant (Table 5). According to the results research by Aisyawati et al (2022) that, the lowest leaf area per plant was found in the treatment without fertilization (treatment A), while between other fertilization treatments there was no significant difference [22]. This shows that the land used is less fertile so it is very IOP Publishing doi:10.1088/1755-1315/1253/1/012023 6 responsive to the application of fertilizer, although the variation in the increase in leaf area per plant is not significantly different between the doses of fertilization given to sweet corn plants.…”
Section: Plant Growth and Yieldmentioning
confidence: 88%